Geographical Indication Protection of Tenun Gringsing Bali Fabric as A Society Cultural Heritage in Tenganan Pegringsingan - Kurniawan, I Gede Agus; Adi Sudharma, Kadek Januarsa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 3 (2021), 2021)
The Kain Tunun Gringsing Bali is a cultural heritage of the people of Tenganan Pegringsingan Village and has a philosophical value and sacred meaning behind every motif of the Balinese Tunun Gringsing cloth. In October 2016 the government has issued a Geographical Indication Protection certification for the Bali Gringsing Tunun Fabric. The purpose of writing this paper is to examine the granting of Geographical Indication Certificates to Bali Gringsing Tunun Fabrics both in terms of production and sales. The research in this article uses empirical legal research methods. The results of the study found that the evaluation after obtaining a protection certificate showed that there was no significant impact on the productivity of the Balinese Tunun Gringsing fabric craftsmen. This is due to the lack of socialization after and data collection so that it cannot be done in a concrete way the perceived impact of getting the exclusive right to protect the geographical indications of the Kain Tunun Gringsing Bali